Does economics add up? An introduction to meta-regression analysis - Tom D. Stanley (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
Meta-analysis is the statistical analysis of an entire empirical literature. It seeks to summarize, evaluate and analyse what we know about a given empirical question, phenomenon, or effect. Meta-regression analysis (MRA) is meta-econometrics, uses the very tools that produce economics research, and provides a rigorous, objective alternative to conventional narrative reviews in economics. MRA often reveals surprising truths about economics. To illustrate these methods, I discuss meta-analyses of the employment effect of the minimum wage, efficiency wages, the natural rate hypothesis and unemployment hysteresis, the last two of which provide a rigorous, empirical falsification of the natural rate hypothesis.
Keywords: E00; 330; meta-regression analysis; empirical economics; minimum wage; efficiency wage; natural rate hypothesis